ANALISIS PROBLEMATIKA GURU DALAM PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA DI TINGKAT SD - Musdalifah; Moch. Bahak Udin By Arifin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this research is to find out the problems of teachers in developing multimedia-based learning media. so that, in the future teachers will be able to evaluate and increase their insight and be able to apply multimedia-based learning in the right way. The method used in this research is descriptive qualitative data collection techniques derived from interviews , observation and documentation . This research was conducted at SD Negeri Badal 1 Ngadiluwih Kediri. The results of the research are that teachers are not yet proficient in digital skills, time management takes a long time when the learning process is multimedia-based, digital gaps, updates to technological devices or infrastructure are less than optimal.